- The report of the Parliamentary Commission of Enquiry about the phenomenon of organized kidnappings. (Rivista di Studi e Ricerche sulla criminalità organizzata, 2017)
The section “History and Memory” gives an account of a selection of excerpts from the report of the Parliamentary Commission of Enquiry about the phenomenon of organized kidnappings.The Commitee of experts, specially set up by Ottaviano Del Turco and coordinated by Alessandro Pardini, drawn up a report which was approved on October 7th, 1998. It represents the first institutional document specifically addressed to a phenomenon which has marked dramatically italian history in the ‘70s and ‘80s.The excerpts we have selected concern the different types of kidnappings in Italy and provides a statistical overview of the trends of the phenomenon from 1969 to 1998. Moreover they deal with the kidnappings of Giuseppe Soffiantini and Alessandra Sgarella.Keywords: kidnappings, hostages, blackmailing, ransom, Parliamentary Commission of Enquiry.